Development of Creative Imagination Through the Study of Paul Verlaine's Lyric Poetry: A Pedagogical Approach for Literature Education (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2024)
This article examines the development of creative imagination through studying lyric poetry, particularly Paul Verlaine's works, in secondary literature education. The study focuses on lyric poetry as a form that enriches students' inner world, develops creative imagination, and forms aesthetic sensibilities. The research provides a scientific-methodological analysis of creative imagination development in foreign literature lessons and develops pedagogical guidelines for studying Verlaine's poetic world as a representative of literary impressionism. The article explores creative imagination as both a psychological and pedagogical challenge, distinguishing between reproductive and creative imagination types. Specific techniques and tasks are presented for engaging students in creative activities during poetry study, including practical recommendations for 10th-grade lessons on Verlaine's impressionist poetry. The choice of Verlaine's work is justified by impressionism's aesthetic reliance on reproducing impressions and moods, which appeals to readers' imaginative and emotional capacities. The study presents effective methods including image accumulation, associative exercises, and reproductive tasks with creative elements. The proposed non-traditional lesson format with alternative presentation methods aims to weaken concentrated attention patterns, thereby activating students' imagination. This approach aligns with curriculum requirements while developing students' creative individuality, artistic-imaginative thinking, and intellectual abilities.
Keywords: creative imagination; lyric poetry; Paul Verlaine; literary impressionism; pedagogical methodology; aesthetic education; secondary education; French literature